Intergenerational Transmission and Rental Occupancy Behavior in Family Firms - Xu, Mingxuan; Chen, Baihe (Transactions on Economics, Business and Management Research, 2024)
As more and more family firms enter the stage of intergenerational inheritance, the impact of second-generation family successors on business operations at the early stage of succession has attracted widespread attention and heated debate. Based on this, this paper analyzes and examines the changes in corporate rental occupancy behavior from the perspective of intergenerational succession events of family firms by taking Chinese family-held listed companies as the research object from 2010 to 2022. The results find that the rent-taking behavior of family firms is significantly suppressed after the second-generation successors take office. Through the analysis of the influence mechanism, it is found that the influence of intergenerational succession of family firms on the level of rent occupancy has an incentive effect in the way of exacerbating financing constraints and a disincentive effect in the way of lowering the level of risk-taking, with the disincentive effect being dominant. Further, the inhibitory effect of intergenerational inheritance on firms' rent-taking behavior is weakened when there is intense competition in the industry, a high percentage of the chairman's shareholding, and a low level of educational attainment of the successor. The research work in this paper not only enriches the relevant literature, but also the relevant findings have important implications for the monitoring and control of irregularities in family firms.